Implementation Implementation of a File Security System Using the AES Algorithm to Secure Personal Files: Implementasi Sistem Keamanan File Menggunakan Algoritma AES untuk Mengamankan File Pribadi - Saripa Saripa (Progressive Information, Security, Computer, and Embedded System, 2024)
In this growing digital age, data security is becoming increasingly important as more and more information is stored in digital files which are vulnerable to attacks and unauthorized access. To protect the privacy and confidentiality of personal information, an effective and reliable file security system is required. One effective way is to use cryptographic algorithms such as Advanced Encryption Standard (AES) which have been widely used in various applications that require a high level of security. Implementation of a file security system using the AES algorithm can be an effective and reliable solution for securing personal document files from attacks and unauthorized access and maintaining the privacy and confidentiality of personal information. This study uses the method of Literature Study, Design & Analysis, Implementation, and Testing to analyze and implement the AES algorithm using the PHP programming language and MySQL database. The results showed that the AES algorithm can guarantee the security of the six types of files tested, namely images, Word documents, PDF, Excel and PowerPoint. The AES algorithm can be an effective choice for securing document and image data safely and reliably.